PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP KEPUASAN KERJA DAN DAMPAKNYA TERHADAP KINERJA KARYAWAN PT. (PERSERO) PLN DI PALEMBANG - Lusia Nargis; Kamariah .; Nina Fitriana (JURNAL KOMPETITIF, 2018)
The goal of this research is to know training and education programs that influence job satisfaction and the impact to employee performance in the PT.(Persero) PLN Palembang. This research was conducted by using sampling jenuh method to collect data from employee in the PT.(Persero) PLN Palembang. Data was analized by using Path Analysis. Result of this research shows that direct effect training and education and job satisfaction to employee performance is 1,875, 0,937 and 2,295. Indirect effect training and education to employee performance is 2,348 and by job satisfaction is 0,076. Influence of training and education to employee performance is 3,318, and by job satisfaction had total effect is 2,328, while influence of training and education, job satisfaction to employee performance each is 0,187, 0,937 and 2,295. The most dominant variable influencing employee performance is job satisfaction. Influence other variable outside of models to employee performance is 0,481.     Key words: Training and Education, Job Satisfaction and Employee Performance